MENGAKRABI MANAJEMEN STRATEJIK: SOLUSI MEMBERDAYAKAN ORGANISASI SECARA KOMPREHENSIF - Yani, Asep Tapip (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2010)
Strategic management is an integral part of management science. It appeared as a solution for empowering corporate holistically to establish the comprehensive and systematic organization’s vision and mission. It has been applied for along time in business organization or corporate. Strategic management is challenging because it is far more than simply setting goals and then ordering organization members to attain those goals. An organization’s strategic direction depends upon a variety of considerations. Among them are top management’s assessment of the external environment’s opportunities and threats, andmanagement’s analysis of the firm’s internal strengths and weaknesses. Senior executives are authorized to determine the mission and goals of the firm in the context of external opportunities or threats and the internal strengths or weaknesses. Simultaneously, the top management team must take into account the competing desires and needs of the organization’s various stakeholders (or interested parties) because their support is essential to succesfull strategy implementation. The issues and processes discussed are ones that are directly relevant to all types of organizations, large or small, international or domestic, diversified or single product, and profit or nonprofit likes government organization. The material contained herein should provide keen insight into strategic management and appreciation of its vital role in enhancing organizational effectiveness.